Perbandingan Pengaruh Agen Plasmid Curing Acriflavine dan Acridine Orange (AO) terhadap Laju Plasmid Curing dengan Kuantifikasi Fluoresensi Ekspresi Protein GFP pada Bakteri Escherichia Coli PRSET-emGFP - Jonathan Harris Gultom; Azka Fathiya; Ajeng Farahita Auria; Ayodya Kuncoroadi Y W; Nadhira Azzahra Arandri; Ahmad Hafiz Husamuddin Rahman (P2M Politeknik Pertanian Negeri Samarinda, 2022)
Plasmid curing is an activity to remove plasmids in a bacterium. Plasmid itself is a structure that can carry genes that are beneficial for bacteria, such as making the bacteria resistant to antibiotics. Acridine Orange (AO) and Acriflavine are intercalating agents that function to break down the super helical shape of plasmid DNA and then form circular or open linear plasmid DNA which is used to carry out Plasmid Curing in this study and then compare its effect on the rate of plasmid curing by fluorescence quantification of GFP protein expression. on Escherichia coli PRSET-emGFP bacteria. The results obtained from this experiment were the rate of plasmid loss per generation obtained by measuring the activity of the GFP reporter on the recombinant E. coli model given the curing agent Acridine Orange was 9.52% for the AO 50 treatment, 44.2% for the AO 100, 10.4% for the AO 50 treatment. Akriflavina 250, and 0.836% for Acriflavine 125. Therefore, it can be concluded that the Acridine Orange treatment was more effective than the Acriflavine treatment against the pRSET-EmGFP recombinant E. coli curing plasmid.